Effects of antidepressant treatments on health service utilization and medical costs among patients with depression: a nationwide population-based retrospective cohort study in Taiwan. (July 2019) - Su, Kuan-Pin; Tang, Chao-Hsiun; Chang, Hui-Chih; Chiu, Wei-Che; Lu, Ning; Huang, Kuo-Cherh
Abstract : This study aimed to assess the associations between the use of different types of antidepressants and health service utilization and costs among depressed patients. Data used in this study were retrieved from the Taiwan National Health Insurance Research Database. We identified 447 411 new antidepressant users during the study period (2011–2015) and they were individually followed for a 1-year period. Two-part generalized estimating equation models were conducted. Results demonstrated that there was a substantial decrease in outpatient service utilized by patients undertaking serotonin antagonists and reuptake inhibitors ( β = −0.2074), serotonin–norepinephrine reuptake inhibitors ( β = −0.0452), tricyclic antidepressants ( β = −0.1308), or other antidepressants ( β = −0.0637), compared with their counterparts in the selective serotonin reuptake inhibitors group (all P < 0.05). Compared with patients who were treated with selective serotonin reuptake inhibitors, those who were prescribed serotonin antagonists and reuptake inhibitors ( β = −0.4934, P < 0.05) or tricyclic antidepressants ( β = −0.4194, P < 0.05) had incurred lower costs pertaining to outpatient service, while considerably higher costs were borne by those patients embarked on the treatment of serotonin–norepinephrine reuptake inhibitors ( β = 0.3228, P < 0.05) or other antidepressants ( β = 0.1118, P < 0.05). We concluded that the initiation of various classes of antidepressants led to significant variations in health service utilization and costs among depressed patients.